Answer:
Step-by-step explanation:
6x∧2-7x-3=0
the coefficient of x² multiplied by -3 = -18
we need to look for 2 numbers that when we add it to together it will equate to -7x
+2 and -9 is the answer
6x∧2+2x-9x-3=0
2x(3x+1)-3(3x+1)=0
(2x-3)(3x+1)=0
equate each brackets to 0
2x-3=0 3x+1=0
2x=3 3x=-1
x=3/2 x=-1/3
Answer: C
Y=90+6x/x
90 new tools + 6 dollars (x) over x dollars
Answer:
4
Step-by-step explanation:
2x - 1 = 7
2x = 8
x = 4
Answer:
see below
Step-by-step explanation:
y = 8x − 9
y = 4x − 1
Since the two equations are both equal to y set them equal to each other
8x -9 = 4x-1
Subtract 4x from each side
8x - 9 -4x = 4x-1-4x
4x -9 = -1
Add 9 to each side
4x-9+9 = -1+9
4x = 8
Divide by 4
4x/4 = 8/4
x=2
Now find y
y =4x-1
y = 4(2) -1
y = 8-1
y = 7
(2,7)
The solution to the system of equations is where the two lines intersect. When the two lines are graphed, they will intersect at (2,7)